Analisis Kinerja Petugas Avsec Dalam Pemeriksaan Barang Penumpang Pada Mesin X-Ray Di Bandar Udara Udara Sultan Muhammad Salahuddin Bima - Indri Andriani; Faiz Albanna (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is based on the background of rule violations that often occur by officers during On The Job Training (OJT) at Sultan Muhamad Salahuddin Bima Airport, for example, such as not being on time and wearing incomplete uniforms. The purpose of this study was to determine the performance strategy of AVSEC officers in checking passenger goods on X-Ray machines and how AVSEC officers handle malfunctioning X-Ray machines. The method used is qualitative with a descriptive approach. The data collection techniques are observation, interviews, documentation and using SWOT analysis variable weighting. Respondents in this study were security officers in the X-Ray machine section of the Aviation Security unit at Sultan Muhammad Salahuddin Airport in Bima. The results of this study are: 1). The performance strategy of AVSEC officers in checking passenger goods on X-Ray machines at Sultan Muhammad Salahuddin Airport is in accordance with existing handling standards and can support the continuity of discipline of duties and responsibilities that are better. 2). The way AVSEC officers handle malfunctioning X-Ray machines at Sultan Muhammad Salahudin Airport in Bima is by checking goods manually using Walk Through Metal Detector (WTMD) and Hand Held Metal Detecor (HHMD) machines. The performance strategy of Aviation Security officers shows in quadrant one, namely aggressive growth (grow oriented strategy).